Transition metal catalyzed C(sp2)-C and C(sp2)-N bond forming reactions - Maraswami, Manikantha (2018)
The thesis describes the development of transition metal catalysed C-H functionalization of C(sp2)-H bonds of arenes and their application in organic synthesis. In the first chapter, recent advancements in the transition metal catalysed sp2 C-H functionalization of aromatic compounds by the installation of directing groups like amide, carbamate and ketimines are described concisely. In the second chapter, a general protocol for iridium catalyzed direct C-H amidation of cyclic N-sulfonyl ketimines using sulfonyl, acyl and aryl azides as nitrogen source is discussed. Benefiting from the robustness and high efficiency of this transformation, a variety of functional groups were well tolerated during this mild process. With the use of sultams as directing group, monoamidation products can be produced efficiently in excellent ortho-selective manner, providing a simple method for the synthesis of biologically relevant aminosultam compounds. In the third chapter, we reported a synthetic protocol for the trifluoroethylation of N-alkyl benzamides with mesityl(2,2,2-trifluoroeth-yl)iodonium salt. The very mild reaction condition employed allows a compatibility of a vast variety of synthetic useful functional groups. Further, we isolated the dimeric palladacycle complex with arene amide and carried out some mechanistic studies. In chapter four, we described a new synthetic route to meta-arylated phenol and its derivatives. We achieved this transformation by employing cheap copper catalyst under mild conditions using phenol carbamates and diaryliodonium salts as coupling partners. The reported method is compatible with a broad range of phenols as well as diaryliodonium salts. The meta-arylated carbamate products obtained from this reaction can be further functionalized to get multisubstituted biaryl systems.